Hepcidin predicts response to IV iron therapy in patients admitted to the intensive care unit: A nested cohort study - Litton, E.; Baker, S.; Erber, W.; Farmer, Shannon; Ferrier, J.; French, C.; Gummer, J.; Hawkins, D.; Higgins, A.; Hofmann, A.; De Keulenaer, B.; McMorrow, J.; et al. (2018)
© 2018 The Author(s). Background: Both anaemia and red blood cell (RBC) transfusion are common and associated with adverse outcomes in patients admitted to the intensive care unit (ICU). The aim of this study was to determine whether serum hepcidin concentration, measured early after ICU admission in patients with anaemia, could identify a group in whom intravenous (IV) iron therapy decreased the subsequent RBC transfusion requirement. Methods: We conducted a prospective observational study nested within a multicenter randomized controlled trial (RCT) of IV iron versus placebo. The study was conducted in the ICUs of four tertiary hospitals in Perth, Western Australia. Critically ill patients with haemoglobin (Hb) of <100g/L and within 48h of admission to the ICU were eligible for participation after enrolment in the IRONMAN RCT. The response to IV iron therapy compared with placebo was assessed according to tertile of hepcidin concentration. Results: Hepcidin concentration was measured within 48h of ICU admission in 133 patients. For patients in the lower two tertiles of hepcidin concentration (<53.0µg), IV iron therapy compared with placebo was associated with a significant decrease in RBC transfusion requirement [risk ratio 0.48 (95% CI 0.26-0.85), p=0.013]. Conclusions: In critically ill patients with anaemia admitted to an ICU, baseline hepcidin concentration predicts RBC transfusion requirement and is able to identify a group of patients in whom IV iron compared with placebo is associated with a significant decrease in RBC transfusion requirement.